Characterization and utilization of reed stem as a lignocellulosic resource for particleboard production - Kord, Behzad; Roohani, Mehdi; Kord, Behrouz (Maderas. Ciencia y Tecnología, 2025)
The objective of this study was to investigate the use of the reed stem in manufacturing three-layer particleboard. Variable factors were mixing ratio of reed and industrial wood particles (0:100, 25:75, 50:50, 75:25 and 100:0 in the surface and middle layers), press temperature (170, 180, 190 °C) and pressing cycle time (5, 6, 7 min). Other parameters such as resin content (8% in core and 10% in faces), hardener content (2%), press closing rate (4,5 mm/min), press pressure (30 kg/cm2), board thickness (15 mm), and target density (700 kg/m3) were held constant. The physical and mechanical properties of particleboard panels including modulus of rupture, modulus of elasticity, internal bonding, water absorption and thickness swelling were determined according to the procedures of European standards. The results showed that modulus of rupture, modulus of elasticity, internal bond, water absorption and thickness swelling increased with the increase of reed particles content. The positive influence of press temperature and press time can also be seen in terms of improved physical and mechanical properties. Based on the findings of this study, we can conclude that reed stem can be used to manufacture particleboard.